Explorations of a Mind-Traveling Sociologist - Fox, Renée C.; Fadiman, Anne. (London : Anthem Press, 2019)
"Explorations of a Mind-Traveling Sociologist" is a book of thematically interconnected ethnographic essays by the internationally esteemed sociologist Renée C. Fox, who employs a participant observer outlook to provide insight on enduring--and pressing--issues of geopolitics, epidemics, aging, friendship and humanitarian action and on the meaning and meaningfulness of teaching, exploring, questing and writing.
Chapter 11 Miss Balkema-and MarybethChapter 12 Life, Death and Uncertainty in Physicians' Memoirs; Part 4 Encounters with Current Events; Chapter 13 Terrorist Bombings in Brussels; Chapter 14 The 2016 Presidential Election; Chapter 15 Donald Trump's Executive Orders on Immigration; Part 5 On Being a Teacher; Chapter 16 On Being a Teacher; In Memoriam; Chapter 17 What I Learned about the Language of Silence; Chapter 18 A Bioethics Award and a Surrogate Lecture; End Matter; Epilogue; Index
Print version record.
JSTOR
Keywords: Sociology; Social medicine; Sociology; Sociologie; sociology; SOCIAL SCIENCE / Anthropology / Cultural & Social; MEDICAL / Diseases; SOCIAL SCIENCE / Sociology / General; Social medicine; Sociology